Geological factors in the Villa Wetlands - Chacón Abad, Néstor (2010)
In recent years, the so-called wetlands have been investigated, as habitats sensitive to environmental management and their impact on the ecosystem, in this investigation the geological aspects of the origin and continuity of the waters in the Villa Pantanos are considered, to to be able to carry out a future efficient management of this water resource, which is of vital importance to maintain the balance of the local ecosystem. The study area was considered by tectonic criteria (faulting) as a continuity of the deepest water tables of the southern sector of the dejective range of the Rímac river, which has enabled the waters in the Villa swamps to have had an adequate recharge. However, in the last 5 decades on the cliffs of the Chorrillos Sector Beach Circuit of the Costa Verde Project, it has been observed that a notable decrease in the water table has occurred. The records of artesian wells located in the southern sector of the Rímac River dejective range indicate various levels of permeable materials.